A compact tritium enrichment unit for large sample volumes with automated re-filling and higher enrichment factor. (December 2016) - Kumar, B.; Han, L.-F.; Wassenaar, L.I.; Klaus, P.M.; Kainz, G.G.; Hillegonds, D.; Brummer, D.; Ahmad, M.; Belachew, D.L.; Araguás, L.; Aggarwal, P.
Abstract: Tritium ( 3 H) in natural waters is a powerful tracer of hydrological processes, but its low concentrations require electrolytic enrichment before precise measurements can be made with a liquid scintillation counter. Here, we describe a newly developed, compact tritium enrichment unit which can be used to enrich up to 2 L of a water sample. This allows a high enrichment factor (>100) for measuring low 3 H contents of <0.05 TU. The TEU uses a small cell (250 mL) with automated re-filling and a CO2 bubbling technique to neutralize the high alkalinity of enriched samples. The enriched residual sample is retrieved from the cell under vacuum by cryogenic distillation at −20 °C and the tritium enrichment factor for each sample is accurately determined by measuring pre- and post- enrichment 2 H concentrations with laser spectrometry. Highlights: A compact tritium enrichment unit/system for achieving high enrichment factor. Electrolytic cell capacity only 250 mL to enrich water sample up to 2 L in one run. Automated filling of water sample from reservoir to cell. Alkalinity neutralization and post distillation directly from cell. Precise estimation of tritium enrichment factor using deuterium enrichment.